2013
DOI: 10.1021/sb300116y
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Activity Assessment of Terminator Regions in Saccharomyces cerevisiae Provides a ″Terminatome″ Toolbox

Abstract: The terminator regions of eukaryotes encode functional elements in the 3' untranslated region (3'-UTR) that influence the 3'-end processing of mRNA, mRNA stability, and translational efficiency, which can modulate protein production. However, the contribution of these terminator regions to gene expression remains unclear, and therefore their utilization in metabolic engineering or synthetic genetic circuits has been limited. Here, we comprehensively evaluated the activity of 5302 terminator regions from a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
136
8
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(149 citation statements)
references
References 83 publications
4
136
8
1
Order By: Relevance
“…2d). Consistent with these observations, the heterologous ADH1 terminator used in mNG-II and mSC-II libraries is stronger than terminator sequences of most yeast ORFs 18 . Together these results demonstrate that tagging modules with heterologous terminators, commonly used for C-terminal protein tagging in yeast 19,20 , can measurably impact protein expression and suggest applications of the C-SWAT library to study regulation of gene expression.…”
supporting
confidence: 67%
“…2d). Consistent with these observations, the heterologous ADH1 terminator used in mNG-II and mSC-II libraries is stronger than terminator sequences of most yeast ORFs 18 . Together these results demonstrate that tagging modules with heterologous terminators, commonly used for C-terminal protein tagging in yeast 19,20 , can measurably impact protein expression and suggest applications of the C-SWAT library to study regulation of gene expression.…”
supporting
confidence: 67%
“…Although the constructs were controlled by the same promoter/terminator systems for both the yeast and E. faecalis modules (Fig. 2a), differences in mRNA levels may be due to stability of different transcripts (especially considering that the E. faecalis genes are not native genes while the yeast genes are native), or to idiosyncratic characteristics of the ORFs/constructs and their compatibility with specific promoters and terminators (Carquet et al, 2015;Yamanishi et al, 2013). Regardless of the mechanism, these data demonstrate that expression of the yeast genes is limited at the RNA level relative to the E. faecalis genes.…”
Section: Increasing Trans-nerolidol Production By Enhancing the Mva Pmentioning
confidence: 99%
“…Nevertheless, recent work in S. cerevisiae has aptly demonstrated that varying the choice of native terminators can influence mRNA half-life of heterologously expressed genes and result in increased or decreased protein levels (5)(6)(7) . The underlying force responsible for these variations in gene expression is disparate stabilizing elements found in different native terminators (2,8) .…”
mentioning
confidence: 99%